Proceedings of IEEE International Test Conference - (ITC)
DOI: 10.1109/test.1993.470641
|View full text |Cite
|
Sign up to set email alerts
|

I/sub DD/ pulse response testing on analog and digital CMOS circuits

Abstract: lhis paper presents a new method for detecting defect and fabrication variations in both digital and analog CMOS circuits by simultaneously puking the power supply raik and analyzing the temporal andlor the spectral characteristics of the resulting transient rail currents. lhe method presented has a distinct advantage over other forms of iDD testing because it requires a single test vector to excite and expose the presence of a defect or irregular fabrication process condition. lhis paper presents data fhom si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Nontarget tests, such as at-speed Boolean methods, are the only tests available. Other tests, such as the transient power supply current test, i,l,x, require further research to describe their capabilities [74,75].…”
Section: Defect Class Testingmentioning
confidence: 99%
“…Nontarget tests, such as at-speed Boolean methods, are the only tests available. Other tests, such as the transient power supply current test, i,l,x, require further research to describe their capabilities [74,75].…”
Section: Defect Class Testingmentioning
confidence: 99%
“…This method provides a high fault coverage at a lower testing cost. Similar techniques have been proposed for mixedsignal circuits, [7], [8]. These methods involve monitoring the power supply current (IDD) waveform of the circuit under test (CUT) and comparing it with the waveform produced by the fault-free circuit.…”
Section: Introductionmentioning
confidence: 99%
“…It appeared [6] that our method could detect faults that are undetected by IDDQ testing, such as stuck-open faults [3]. Moreover, IDDQ testing is limited to technologies with zero or very small quiescent currents [4]. As it is explained later, the applicability of our method should not be limited only to these technologies.…”
mentioning
confidence: 98%
“…Our method is different since only a small part (DC and first harmonic) of the frequency spectrum is estimated using a simple FFT on a few current samples. Beasley et al [4] presented a method which pulses VDD and GND signals while the inputs are siet t o a fixed bias voltage. In their paper, they showed that the supply current frequency spectrum of a defective circuit varied a defect-free circuit without proposing any method t o used this information.…”
mentioning
confidence: 99%
See 1 more Smart Citation